Utility of the World Health Organization Disability Assessment Scale Short Version and the WHO Minimal Generic Data Set Covering Functioning and Health in Assessing Discharge Disposition after Sub-acute Stroke Rehabilitation - Tarvonen-Schröder Sinikka; Koivisto Mari (United Kingdom, 2022)
In search for the best instruments that are accurate and efficient in distinguishing discharge dispositions after inpatient rehabilitation post stroke, more studies using varying outcome measures are needed; especially measures with diverse domains including patient and family perceptions and participation instead of just activities of daily living. In this cross-sectional cohort study among 229 consecutive subacute stroke rehabilitants, the utility of two short ICF (International Classification of Functioning, Disability and Health) -based measures in differentiating three discharge categories (rehabilitants discharged into the community without or with service or to an institution) was investigated and compared with two traditionally used outcome instruments. All these instruments, the self-reported 12-item World Health Organization (WHO) Disability Assessment Scale (WHODAS), the 7-item WHO minimal generic data set covering functioning and health, Functional Independence Measure (FIM) and modified Rankin Scale differentiated the three discharge categories. No WHODAS proxy responses were missing, but thirty patients were not fit to respond themselves. Significant differences were found in all component, domain and item level comparisons between the subgroups discharged home and those institutionalized in proxy ratings, some fewer in patient ratings. The items that differentiated all three discharge categories in both patient and proxy ratings were standing, walking, washing, dressing and household activities. The accuracy of WHODAS proxy sum and FIM total score at discharge for predicting institutionalization were high (AUC WHODAS 0.88 and FIM 0.95), the optimal cut-off scores being 30 and 80 points, respectively. WHODAS-12 is recommended for determining discharge destination and allocation of social services.